Research on operating parameters of T-groove cylindrical gas film seal based on computational fluid dynamics. (17th July 2019) - Sun, Junfeng; Liu, Meihong; Xu, Zhen; Liao, Taohong
Cylindrical gas film sealing technology is a new type of dry gas sealing technology. Compared with the face gas film sealing technology, the cylindrical gas film seal presents a strong floating property, which can reduce the vibration and thermal deformation of the rotor system. In this article, the effect of operating parameters such as speed, pressure difference and viscosity on the T-groove gas cylindrical film seal performance are studied in detail by the method of control variable in computational fluid dynamics software, and pressure distribution, gas film stiffness, leakage, leakage stiffness ratio and hydrodynamic force are analysed. Results show that with the increase of the rotational speed, static pressure, hydrodynamic force and film stiffness increase, but leakage decreases first and then increases. Furthermore, the results indicate that with the increase of pressure difference, the static pressure, leakage and hydrodynamic force increase. In addition, the simulations show that when the viscosity increases, the maximum pressure and film stiffness increase, but the leakage decreases. This indicates that as the rotational speed increases, the hydrodynamic effect and the amount of gas overflow in the axial direction increase, resulting in an increase of leakage. Lastly, the results also show that when the pressure difference increases, both the radial and axial gas flow rates increase, resulting in an increase in both the film stiffness and the leakage. With the increase of viscosity, the viscous shear force and fluid hydrodynamic force increase, resulting in the increase of the gas film stiffness. This study can provide a theoretical basis in industrial applications for setting the operating parameters and serving as a reference.